2014
DOI: 10.1002/chem.201402545
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Nanoparticles Bonded to Two‐Dimensional Iron Oxide Graphene Nanosheets: A Synergistic and Highly Reusable Catalyst for the Tsuji–Trost Reaction in Water and Air

Abstract: Low cost, high activity and selectivity, convenient separation, and increased reusability are the main requirements for noble-metal-nanocatalyst-catalyzed reactions. Despite tremendous efforts, developing noble-metal nanocatalysts to meet the above requirements remains a significant challenge. Here we present a general strategy for the preparation of strongly coupled Fe(3)O(4) and palladium nanoparticles (PdNPs) to graphene sheets by employing polyethyleneimine as the coupling linker. Transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 45 publications
0
29
1
Order By: Relevance
“…Besides the k value, the TOF was also calculated and the value was about 0.928 s −1 . Compared with recent studies with catalysts based on Pd nanoparticles, the TOF value of AC@Fe 3 O 4 @Pd nanocatalyst was also higher than others [ 36 , 41 , 42 ].…”
Section: Resultscontrasting
confidence: 72%
“…Besides the k value, the TOF was also calculated and the value was about 0.928 s −1 . Compared with recent studies with catalysts based on Pd nanoparticles, the TOF value of AC@Fe 3 O 4 @Pd nanocatalyst was also higher than others [ 36 , 41 , 42 ].…”
Section: Resultscontrasting
confidence: 72%
“…In 2014, Wang et al . immobilized Fe 3 O 4 and Pd NPs onto rGO functionalized with polyetheylenimine (PEI) endcapped with 3,4‐dihydroxybenzaldehyde to obtain material 118 (Scheme ) . Both Fe 3 O 4 and Pd NPs resulted well dispersed onto the surface of material 118 as evidenced by TEM analysis.…”
Section: Graphene‐ Graphene Oxide‐ and Reduced Graphene Oxide‐based mentioning
confidence: 99%
“…Su et al . used a similar approach to the one used by Wang et al . to obtain a heterogeneous catalyst resembling material 118 and active in the reduction of 4‐nitrophenol…”
Section: Graphene‐ Graphene Oxide‐ and Reduced Graphene Oxide‐based mentioning
confidence: 99%
“…Concerted catalysis between metal complexes and organic functional groups is a notable strategy to create novel heterogeneous catalysis and a highly efficient technique for molecular transformations . Several research groups have reported Pd, Rh, and Cu complexes immobilized on solid surfaces with organic functionalities for the efficient transformation of organic molecules. In the case of concerted catalysis with Pd complexes, the allylation of nucleophiles was shown to be effectively accelerated by the assistance of a basic amine group: both allylic substrates and nucleophiles were activated by Pd complexes and bases, respectively …”
Section: Figurementioning
confidence: 99%